2014
DOI: 10.1159/000369960
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Assessed in Adolescence and the Later Risk of Stroke in Men: A 33-Year Follow-Up Study

Abstract: Background: Stroke is a common cause of death, and a leading contributor to long-term disability. The cost associated with the disease is great. Several modifiable risk factors for stroke have been found in older cohorts; however, no study to date has investigated the effects of these risk factors from late adolescence. Methods: The study cohort comprised 811,579 Swedish men (mean age, 18 years) that participated in the mandatory military conscription service in Sweden between 1969 and 1986. Some risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 31 publications
6
36
0
1
Order By: Relevance
“…Poor scoring in physical fitness is an important risk factor for cardiovascular disease,1 type 2 diabetes,2 hypertension,3 stroke,4 and mortality 2 5. Aerobic capacity and lean body composition are both negatively associated with risk of type 2 diabetes,6 stroke,4 and cardiovascular as well as all-cause mortality 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor scoring in physical fitness is an important risk factor for cardiovascular disease,1 type 2 diabetes,2 hypertension,3 stroke,4 and mortality 2 5. Aerobic capacity and lean body composition are both negatively associated with risk of type 2 diabetes,6 stroke,4 and cardiovascular as well as all-cause mortality 2.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic capacity and lean body composition are both negatively associated with risk of type 2 diabetes,6 stroke,4 and cardiovascular as well as all-cause mortality 2. Moreover, muscular fitness by the age 18 years has been shown to inversely associate with cardiovascular events and cardiovascular mortality in middle age, independent of the aerobic capacity 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies have shown that >90% of the stroke burden is attributable to modifiable risk factors, such as tobacco smoking, alcohol consumption, poor diet, low physical activity, and hypertension. 1,4 It has been demonstrated that several of these risk factors may be already present in late adolescence, 5 highlighting the potential for early identification and intervention. Recently, a growing body of research has linked cannabis use to stroke, particularly to those occurring before 45 years of age.…”
mentioning
confidence: 99%
“…Neuere Untersuchungen konnten das etwa 2-bis 4-fach erhöhte Schlaganfallrisiko für Diabetespatienten bestätigen, wie eine Evaluation schwedischer Daten aus Wehrdiensttauglichkeitsuntersuchungen zeigte [23]. Bei der Analyse der Schlaganfälle zwischen dem 18. und 50.…”
Section: Epidemiologieunclassified